2015
DOI: 10.1063/1.4933102
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of phase change materials below a capping layer using correlative infrared near-field microscopy and electron microscopy

Abstract: Phase Change Materials (PCM) show two stable states in the solid phase with significantly different optical and electronic properties. They can be switched reversibly between those two states and are promising candidates for future non-volatile memory applications. The development of phase change devices demands characterization tools, yielding information about the switching process at high spatial resolution. Scattering-type Scanning Near-field Optical Microscopy (s-SNOM) allows for spectroscopic analyses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The written and rewritten cIST antennas are visible as depressions in the aIST film (decreased density of crystalline PCMs 59 ), while the erased antenna shows a slight elevation in topography (microbump formation 60 ). With s-SNOM, it is possible to measure the local infrared optical properties of the submicrometer crystalline areas with a resolution that is well below the diffraction limit 61 . The measured near-field optical amplitude signal s 3 at a wavelength of λ = 10.57 µm, referenced to the amplitude signal s 3 (aIST) of the aIST, is shown in the bottom row of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The written and rewritten cIST antennas are visible as depressions in the aIST film (decreased density of crystalline PCMs 59 ), while the erased antenna shows a slight elevation in topography (microbump formation 60 ). With s-SNOM, it is possible to measure the local infrared optical properties of the submicrometer crystalline areas with a resolution that is well below the diffraction limit 61 . The measured near-field optical amplitude signal s 3 at a wavelength of λ = 10.57 µm, referenced to the amplitude signal s 3 (aIST) of the aIST, is shown in the bottom row of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effective charge Q a is thus located slightly higher than the charge Q 0 (located at distance R from the tip apex), indicating that the near-field interaction takes place also via the apex-near part of the tip shaft, which is located further away than the tip apex. Indeed, probing of subsurface layers is frequently attributed to the elongated tip shape, which provides longerreaching evanescent waves (with lower momenta q) that are not captured well by the unmodified FDM for bulk samples 25,39,43 . Note that for large subsurface layer depths d 2 > 30 nm, we observe a dispersive line shape of the nano-FTIR peaks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Despite s-SNOM and nano-FTIR being surface scanning techniques, the finite penetration depth of near fields into the sample allows for subsurface probing of nanoscale structures and defects up to a depth of 100 nm [23][24][25][26][27] . For s-SNOM it has been also shown that depth-resolved information-with the potential of three-dimensional sample reconstruction-can be obtained by analysis of several higher harmonic signals, each of them having a different probing depth [28][29][30][31] .…”
mentioning
confidence: 99%
“…The s‐SNOM technique has already demonstrated that near‐field studies of SiC can distinguish between different polytypes,27a strain,27b and crystalline quality within the Reststrahlen band, suggesting that these near‐field techniques will also allow for insightful characterization of extended defects. Additionally, while the s‐SNOM technique has recently been employed to study fundamental material properties of semiconductors and/or phase change materials other than SiC, such as GaN, hexagonal boron nitride (hBN),24c,d,28,39 vanadium dioxide (VO 2 ), Ge 3 Sb 2 Te 6 (GST),32c and Ag 4 In 3 Sb 67 Te 26 (AIST), a detailed, correlative study of extended defects in wide‐bandgap materials has not been performed up until now.…”
Section: Introductionmentioning
confidence: 99%